Analisis Regresi Model Produktivitas Tenaga Kerja Industri Kecil Keripik Singkong Di Desa Kasarangan Kecamatan Labuan Amas Utara Kabupaten Hulu Sungai Tengah - Miranda Romaully Br. Sitanggang; Syahriati Syahriati (Rawa Sains: Jurnal Sains STIPER Amuntai, 2014)
Productivity level is one measure that determines the success of a company in competition in the business world. Important elements that can increase the total productivity of the company are labor, capital, production, organization and marketing where the most able element to provide the greatest benefits is labor. This study aims to analyze what factors influence labor productivity in the small industry of cassava chips in Kasarangan Village. Based on the research results, the small industry of cassava chips in Kasarangan Village is a simple economic undertaking where the management carried out is still traditional in nature, not yet followed by significant technological developments. The equipment used is still simple equipment and the use of equipment to carry out the production process is still dominated by human power, so labor productivity in the small industry of cassava chips is still relatively low. From the calculation of the coefficient of determination (R2) obtained a value of 50.9%. This means that there is a diversity of labor productivity that can be explained by the variables used. While the remaining 49.1% is explained by other variables not contained in the model. Factors that significantly influence labor productivity are time allocation with a t-count value of 2.423 greater than t-table (2.423> 1.696) with a sig value of 0.021 smaller than alpha (0.021 <0.05). While the factors of age, education, number of dependents, work experience, gender, and employment status (dummy) did not significantly affect labor productivity.